Introduction to Chinese Fiscal System - Riccardi, Lorenzo (Springer Singapore, 2018)
This user-friendly book aims to summarize the principal topics of Chinese Taxation and offers readers a general overview of the Chinese Taxation and informative updates on tax changes. The book provides a variety of facts, figures, graphs and data in an easy-to read table format. Firstly, the book proposes an introduction to taxation and to the Chinese tax system, secondly, it focuses on direct taxes, indirect taxes and other taxes and, in the end, it covers international taxation. Moreover, the book offers a quick overview of the Chinese M&A taxation and of the Chinese Free Trade Zones.